Dual-targeting demulsifier as well as preparation method and application thereof

By using hydrophilic nanomaterials and polyethers crosslinked by polystyrene maleic anhydride in the binary composite flooding production liquid treatment, a dual-functional deemulsifier is formed, which solves the problems of oil-water separation difficulties and complex treatment processes in the prior art, and achieves the synchronous removal of water-in-oil and oil-in-water functions, and avoids the generation of aging oil and sludge.

CN119798905APending Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311305351.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the synchronous removal of the functions of water-in-oil emulsion and oil-in-water emulsion in binary composite flooding processing, resulting in difficulty in separation of oil and water, and aging oil and sludge, which increases the complexity of the treatment process.

Method used

Polystyrene maleic anhydride (SMA) is used to crosslink the hydrophilic nanomaterials and polyethers to form a deemulsifying agent that bifunctionally functions of nanomaterials and polyethers. This deemulsifying agent improves molecular weight and deemulsification effect through SMA crosslinking, and achieves the synchronous dehydration of crude oil and wastewater through the surface effect of the nanomaterial and the compatibility of the benzene ring.

Benefits of technology

This dual-targeted deemulsion agent can effectively eliminate water-in-oil and oil-in-water emulsions, achieve rapid separation of oil and water, avoid the generation of aging oil and sludge, and simplify the treatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798905A_ABST
    Figure CN119798905A_ABST
Patent Text Reader

Abstract

The invention discloses a dual-targeting demulsifier, which is formed by respectively crosslinking anhydride groups in polystyrene maleic anhydride with a hydrophilic nano-material and polyether, and the dual-targeting demulsifier is composed of a structural unit A from polystyrene maleic anhydride, a structural unit B from the hydrophilic nano-material and a structural unit C from polyether, based on the total mass of the dual-targeting demulsifier, the content of the structural unit A is 10-62.5 wt%, the content of the structural unit B is 7.1-25 wt%, and the content of the structural unit C is 25-80 wt%. The invention also discloses a preparation method and application of the dual-targeting demulsifier. The dual-targeting demulsifier disclosed by the invention has the functions of synchronously realizing crude oil dehydration and sewage oil removal under the synergistic effect of the nano material and a large amount of styryl; as the molecular structure of the demulsifier does not contain positive ions, binary flooding produced liquid cannot react with substances with negative electricity in sewage, and generation of aged oil and oil sludge is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oilfield chemistry, and in particular to a dual-target demulsifier and a preparation method and application thereof. Background Art

[0002] Binary composite flooding refers to a tertiary oil recovery technology that uses a mixed solution of surfactants and polymers as oil-displacing agents. It can greatly improve crude oil recovery on the basis of water flooding, and plays an important role in maintaining stable production in my country's oil fields in the middle and late stages.

[0003] The binary composite flooding process will produce a large amount of produced fluid with complex components and stable properties. Its emulsification type is complex and the emulsification degree is high. This is because the residual polymer in the produced fluid increases the viscosity of the produced water, and the return surfactant and the active components such as colloid and asphalt in the crude oil cause the oil and water to be seriously emulsified, making it difficult to separate the oil and water. Therefore, it is necessary to add functional agents to break the oil-water emulsion-demulsifiers and reverse demulsifiers to the produced fluid to achieve rapid separation of oil and water. The process is roughly divided into two steps: crude oil dehydration and sewage oil removal, that is, using demulsifiers to break the oil-in-water-based crude oil emulsion and using reverse demulsifiers to break the oil-containing sewage emulsion that is mainly oil-in-oil.

[0004] Oil-soluble polyether demulsifiers are usually used to demulsify and dehydrate oil-in-water crude oil emulsions. The method for treating oily wastewater is to add cationic reverse demulsifiers (water purifiers) and flocculants to remove emulsified crude oil, negatively charged suspended matter and other particles in the wastewater through the method of electrical neutralization reaction-flocculation. Since this electrical neutralization reaction and flocculation technology are non-selective for negatively charged substances and particles in wastewater, they not only react and flocculate with negatively charged emulsified oil, but also react with negatively charged particles such as suspended matter and residual oil displacement polymers in wastewater to form a polymer-containing flocculent mixed with crude oil and solid particles, namely sludge. The generation of sludge seriously affects the normal production of oil fields, causes pipeline blockage, causes the filter to fail to operate normally, and pollutes the environment. In this regard, it is urgent to develop non-ionic reverse demulsifiers to overcome the above-mentioned defects of cationic reverse demulsifiers, but the effect is not ideal. At the same time, adding demulsifier and reverse demulsifier to the produced fluid separately means that for these two functional agents, at least two spaced dosing ports must be set up in the oil-water treatment process, which increases the complexity and management points of the treatment process. Therefore, it is a general trend to develop dual-functional oil-water treatment agents that can simultaneously achieve crude oil dehydration and wastewater oil removal, that is, to simultaneously break oil-in-water emulsions and water-in-oil emulsions, especially non-ionic agents.

[0005] With the development of demulsifier and reverse demulsifier technology, nano demulsifier has attracted attention due to the unique effect of its nanoparticles at the oil-water interface. For example: Chinese patent application CN106219669A discloses a method for preparing a magnetic graphene oxide demulsifier, which is made by loading graphene oxide on its surface with magnetic iron powder as a carrier. Its important invention point is that it can be reused. However, the actual oil-water treatment industry is large-scale, and the adsorption material required for recycling magnetic graphene oxide demulsifier is large in volume, requiring a proper amount of placement space, and it is difficult to achieve industrial application. Chinese patent CN 109054888 B discloses a demulsifier and its preparation method. The preparation method includes: preparing hydroxylated carbon nanotubes; in-situ grafting nano silicon dioxide onto hydroxylated carbon nanotubes to obtain a carbon nanotube / nano SiO2 composite nano demulsifier. The present invention also provides a demulsifier obtained by the above preparation method. However, the application scope of the above technical solution is relatively narrow, and it is aimed at O / W crude oil emulsions with an oil content of 5%-10%. Chinese patent CN 110559691 B discloses a reusable carbon-based nano-emulsifier and a preparation method thereof. The preparation method comprises: reacting carbon nanotubes with a mixed acid solution to obtain oxidized carbon nanotubes containing hydroxyl and carboxyl groups on the surface; grafting nano-TiO2 produced by hydrolyzing an organic titanium precursor onto the surface of the oxidized carbon nanotubes to obtain a reusable carbon-based nano-emulsifier. The present invention also discloses a demulsifier obtained by the above preparation method. However, the application scope of the above technical solution is still relatively narrow, and is only suitable for oily wastewater with an oil content of 1%. For nano-emulsifiers, it is still necessary to expand their application scope, especially to be able to demulsify oil-in-water emulsions, and even to simultaneously treat oil-in-water emulsions and water-in-oil emulsions. Summary of the invention

[0006] Purpose of the invention: In view of the shortcomings of the prior art, the purpose of the present invention is to provide a dual-target demulsifier for binary flooding produced fluid treatment and a preparation method thereof. Hydrophilic nano material (HNM in this application) and polyether are cross-linked by polystyrene maleic anhydride (SMA) to obtain a demulsifier with dual functionalization of nano material and polyether, wherein:

[0007] The polyether in the molecular structure of the demulsifier is itself a highly efficient demulsifier. After being cross-linked by SMA, the molecular weight of the demulsifier is further increased.

[0008] The cross-linked nanomaterials in SMA are hydrophilic nanomaterials, which endow the demulsifier with excellent surface effect, small size effect and macro quantum tunneling effect, thus improving the demulsification effect of the dual-target demulsifier.

[0009] The large number of benzene rings in SMA endow the dual-targeted demulsifier with good compatibility with crude oil. Under the synergistic effect of hydrophilic nanomaterials and a large number of styrene groups, the dual-targeted demulsifier has the function of simultaneously achieving crude oil dehydration and wastewater oil removal. Moreover, since the demulsifier molecular structure does not contain cations, it will not react with negatively charged substances in the wastewater for binary flooding produced fluid, thus avoiding the generation of aged oil and sludge.

[0010] Technical solution: A dual-target demulsifier, which is made by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein:

[0011] The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether;

[0012] Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 10-62.5% by weight, the content of the structural unit B is 7.1-25% by weight, and the content of the structural unit C is 25-80% by weight.

[0013] A method for preparing the above-mentioned dual-target demulsifier, in parts by mass, comprises the following steps:

[0014] (1) reacting 100 parts of a hydrophilic nanomaterial with dopamine hydrochloride or tannic acid or a silane coupling agent, respectively, to obtain a polydopamine-modified nanomaterial or a tannic acid-modified nanomaterial or a silane coupling agent-modified nanomaterial;

[0015] (2) dispersing the polydopamine-modified nanomaterial or the tannic acid-modified nanomaterial or the silane coupling agent-modified nanomaterial in solvent C, and reacting with 100-500 parts of polystyrene maleic anhydride to obtain a nanomaterial grafted with polystyrene maleic anhydride;

[0016] (3) The nanomaterial grafted polystyrene maleic anhydride is dispersed in solvent C and reacted with 200-800 parts of polyether. After the reaction is completed, a dual-target demulsifier is obtained.

[0017] Furthermore, when the product of step (1) is a polydopamine-modified nanomaterial, the specific steps are as follows:

[0018] (11) Take appropriate amounts of dopamine hydrochloride and 100 parts of hydrophilic nanomaterials in a reaction container, respectively, wherein:

[0019] The mass ratio of dopamine hydrochloride to the hydrophilic nanomaterial is (0.1-10):10;

[0020] (12) Add an appropriate amount of Tris-HCl buffer to the reaction container, seal it, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for at least 0.5 h to obtain a mixed solution, wherein:

[0021] The amount of the Tris-HCl buffer is 2-20 times the mass of the hydrophilic nanomaterial;

[0022] (13) transferring the mixed solution obtained in step (12) to an oscillator and oscillating at room temperature for at least 4 h to obtain a reaction solution;

[0023] (14) The reaction solution obtained in step (13) is centrifuged, and then washed with ultrapure water and anhydrous ethanol at least three times, and vacuum dried at 30-60° C. for at least 12 h. After completion, a polydopamine-modified nanomaterial is obtained.

[0024] Furthermore, in step (13), the mixed solution obtained in step (12) is transferred to an oscillator and oscillated at a frequency of 100-300 rpm at room temperature for 4-24 hours.

[0025] Furthermore, when the product of step (1) is a tannic acid-modified nanomaterial, the specific steps are as follows, based on parts by mass:

[0026] S11, taking an appropriate amount of tannic acid and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0027] The mass ratio of the tannic acid to the hydrophilic nanomaterial is (0.1-10):10;

[0028] S12, adding solvent A to the reaction container, sealing, and ultrasonically dispersing the hydrophilic nanomaterial in an ultrasonic oscillator for at least 2 hours to obtain a mixed solution, wherein:

[0029] The amount of solvent A added is 2-20 times the mass of the hydrophilic nanomaterial;

[0030] S13, transferring the mixed solution obtained in step S12 to an oscillator and oscillating at room temperature for at least 4 hours to obtain a reaction solution;

[0031] S14, centrifugally separating the reaction solution obtained in step S13, washing with ultrapure water and anhydrous ethanol at least 3 times in sequence, and vacuum drying at 30-60° C. for at least 12 hours to obtain tannic acid-modified nanomaterials.

[0032] Furthermore, the solvent A is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, 1,4-dioxane, dimethyl sulfoxide, and N-methylpyrrolidone.

[0033] Furthermore, in step S13, the mixed solution obtained in step S12 is transferred to an oscillator and oscillated at a frequency of 100-300 rpm for 4-24 hours at room temperature.

[0034] Furthermore, when the product of step (1) is a silane coupling agent-modified nanomaterial, the specific steps are as follows, calculated by weight:

[0035] Step 11, take an appropriate amount of silane coupling agent and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0036] The mass ratio of the silane coupling agent to the hydrophilic nanomaterial is (0.1-10):10;

[0037] Step 12, add solvent B to the reaction container, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for at least 0.5h to obtain a mixed solution, wherein:

[0038] The amount of solvent B added is 2-20 times the mass of the hydrophilic nanomaterial;

[0039] Step 13, transfer the mixed solution obtained in step 12 to a constant temperature magnetic stirrer, and stir the mixture at 30-100°C for 2-18h to obtain a reaction solution;

[0040] step14. Centrifuge the reaction solution obtained in step13, wash it with ultrapure water and anhydrous ethanol at least 3 times in sequence, and vacuum dry it at 30-60°C for at least 12 hours to obtain a silane coupling agent-modified nanomaterial.

[0041] Furthermore, the solvent B is at least one of methanol, ethanol, n-propanol, isopropanol, formic acid and acetic acid.

[0042] Furthermore, the silane coupling agent is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and diethylenetriaminopropyltrimethoxysilane.

[0043] Furthermore, step (2) comprises the following steps:

[0044] (21) Place polydopamine-modified nanomaterials or tannic acid-modified nanomaterials or silane coupling agent-modified nanomaterials, a catalyst, and 100-500 parts of polystyrene maleic anhydride in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse in an ultrasonic oscillator for at least 0.5 h to obtain a mixed solution, wherein:

[0045] The mass ratio of the polydopamine modified nanomaterial or the tannic acid modified nanomaterial or the silane coupling agent modified nanomaterial, the catalyst, and the polystyrene maleic anhydride is (0.1-1):(0.1-1):1;

[0046] The amount of solvent C added is 2-6 times the amount of polystyrene maleic anhydride used;

[0047] (22) The mixed solution obtained in step (21) is transferred to a constant temperature magnetic stirrer, and the mixture is stirred at 40-120° C. for 4-24 hours. After the reaction is completed, the mixture is centrifuged, and the solid is washed with solvent C for at least 3 times, and vacuum dried at 60-80° C. for at least 12 hours to obtain the nanomaterial grafted polystyrene maleic anhydride.

[0048] Furthermore, the catalyst is one of p-toluenesulfonic acid, sulfuric acid, hydrochloric acid and phosphoric acid.

[0049] Furthermore, the solvent C is at least one of toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, dioxane, dimethyl sulfoxide, and N-methylpyrrolidone.

[0050] Furthermore, the specific steps of step (3) are as follows:

[0051] (31) Place nanomaterial grafted polystyrene maleic anhydride, a catalyst, and 200-800 parts of polyether in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the nanomaterial grafted polystyrene maleic anhydride in an ultrasonic oscillator for at least 0.5 h to obtain a mixed solution, wherein:

[0052] The mass ratio of nanomaterial grafted polystyrene maleic anhydride, catalyst and polyether is (0.1-1):(0.1-1):1;

[0053] The amount of solvent C added is 2-6 times the amount of polyether used;

[0054] (32) The mixed solution obtained in step (31) is transferred to a constant temperature magnetic stirrer, stirred and reacted at 40-120° C. for 4-24 hours. After the reaction is completed, the mixture is centrifuged and washed with distilled water and anhydrous ethanol at least 3 times in sequence, and vacuum dried at 60-80° C. for at least 12 hours to obtain a dual-target demulsifier.

[0055] Furthermore, the molecular weight of the polystyrene maleic anhydride is in the range of 2000-100000.

[0056] Furthermore, based on the mass of the polystyrene maleic anhydride, the content of the structural unit derived from maleic anhydride is 5-50% by weight.

[0057] Furthermore, the hydrophilic nanomaterial is at least one of nano-TiO2, nano-ZnO, nano-SiO2, graphene oxide, and carbon nanotubes.

[0058] Furthermore, the particle size of the nanomaterial is 1-100 nm.

[0059] Further, the polyether is a diblock polyether polymerized with propylene oxide or ethylene oxide using at least one of an alkyl alcohol having 4 to 18 carbon atoms, an alkylamine having 4 to 18 carbon atoms, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethylene imine, phenolamine resin, phenolic resin, and polyamide-amine as an initiator, or

[0060] A triblock polyether polymerized with propylene oxide, ethylene oxide, or propylene oxide using at least one of an alkyl alcohol having 4 to 18 carbon atoms, an alkylamine having 4 to 18 carbon atoms, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethylene imine, phenolamine resin, phenolic resin, and polyamide-amine as an initiator; or

[0061] A triblock polyether prepared by polymerizing at least one of an alkyl alcohol having 4 to 18 carbon atoms, an alkylamine having 4 to 18 carbon atoms, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethylene imine, phenolamine resin, phenolic resin and polyamide-amine as an initiator with ethylene oxide, propylene oxide and ethylene oxide.

[0062] Furthermore, the molecular weight of the polyether is 2000-50000.

[0063] A dual-target demulsifier is prepared by any one of the above preparation methods.

[0064] The application of any of the above dual-target demulsifiers in oil production, especially in the treatment of binary composite flooding produced fluid as a demulsifier.

[0065] Beneficial effects: The dual-target demulsifier disclosed in the present invention and its preparation method and application have the following beneficial effects:

[0066] The dual-target demulsifier structure contains nanomaterials, demulsifiers and a large number of benzene rings at the same time, wherein the nanomaterials give the dual-target demulsifier excellent surface effect, small size effect and macro quantum tunneling effect, and the large number of benzene rings give the dual-target demulsifier good compatibility with crude oil. Under the synergistic effect of the nanomaterials and a large number of styrene groups, the dual-target demulsifier has the function of simultaneously realizing crude oil dehydration and sewage oil removal.

[0067] Because the demulsifier does not contain cations in its molecular structure, it will not react with negatively charged substances in the sewage in the binary flooding produced fluid, thus avoiding the generation of aged oil and sludge. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 The present invention discloses a flow chart of a method for preparing a dual-target demulsifier. DETAILED DESCRIPTION

[0069] The specific embodiments of the present invention are described in detail below.

[0070] In this application document: hydrophilic nano material (HNM for short in this application).

[0071] Example 1

[0072] A dual-target demulsifier, which is formed by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein:

[0073] The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether;

[0074] Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 10% by weight, the content of the structural unit B is 10% by weight, and the content of the structural unit C is 80% by weight.

[0075] Example 2

[0076] A dual-target demulsifier, which is formed by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein:

[0077] The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether;

[0078] Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 10% by weight, the content of the structural unit B is 25% by weight, and the content of the structural unit C is 65% by weight.

[0079] Example 3

[0080] A dual-target demulsifier, which is formed by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein:

[0081] The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether;

[0082] Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 62.5% by weight, the content of the structural unit B is 7.1% by weight, and the content of the structural unit C is 30.4% by weight.

[0083] Example 4

[0084] A dual-target demulsifier, which is formed by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein:

[0085] The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether;

[0086] Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 62.5% by weight, the content of the structural unit B is 12.5% ​​by weight, and the content of the structural unit C is 25% by weight.

[0087] Example 5

[0088] A dual-target demulsifier, which is formed by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein:

[0089] The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether;

[0090] Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 45% by weight, the content of the structural unit B is 25% by weight, and the content of the structural unit C is 30% by weight.

[0091] Example 6

[0092] A method for preparing a dual-target demulsifier, by parts by mass, comprises the following steps:

[0093] (1) reacting 100 parts of a hydrophilic nanomaterial with dopamine hydrochloride to obtain a polydopamine-modified nanomaterial;

[0094] (2) dispersing the polydopamine-modified nanomaterial in solvent C and reacting it with 100 parts of polystyrene maleic anhydride to prepare nanomaterial grafted polystyrene maleic anhydride (SMA-g-HNM);

[0095] (3) The nanomaterial grafted polystyrene maleic anhydride is dispersed in solvent C and reacted with 200 parts of polyether. After the reaction is completed, a dual-target demulsifier is obtained.

[0096] Furthermore, the specific steps of step (1) are as follows:

[0097] (11) Take appropriate amounts of dopamine hydrochloride and 100 parts of hydrophilic nanomaterials in a reaction container, wherein:

[0098] The mass ratio of dopamine hydrochloride to hydrophilic nanomaterial is 0.1:10;

[0099] (12) Add an appropriate amount of Tris-HCl buffer to the reaction container, seal it, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for 0.5 h to obtain a mixed solution, wherein:

[0100] The amount of the Tris-HCl buffer is twice the mass of the hydrophilic nanomaterial;

[0101] (13) transferring the mixed solution obtained in step (12) to an oscillator and oscillating at room temperature for 4 hours to obtain a reaction solution (dopamine hydrochloride is polymerized to form polydopamine hydrochloride, which adheres to the surface of the hydrophilic nanomaterial, and the catechol groups in the polydopamine hydrochloride react with the hydroxyl groups on the surface of the hydrophilic nanomaterial to achieve loading);

[0102] (14) The reaction solution obtained in step (13) is centrifuged, then washed three times with ultrapure water and anhydrous ethanol, and vacuum dried at 30° C. for 24 h. After completion, a polydopamine-modified nanomaterial is obtained.

[0103] Furthermore, in step (13), the mixed solution obtained in step (12) is transferred to an oscillator and oscillated at a frequency of 100 rpm at room temperature for 24 hours.

[0104] Furthermore, step (2) comprises the following steps:

[0105] (21) Place polydopamine-modified nanomaterials, a catalyst, and 100 parts of polystyrene maleic anhydride in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the mixture in an ultrasonic oscillator for 0.5 h to obtain a mixed solution, wherein:

[0106] The mass ratio of polydopamine modified nanomaterial, catalyst, and polystyrene maleic anhydride is 0.1:0.1:1;

[0107] The amount of solvent C added is twice the amount of polystyrene maleic anhydride used;

[0108] (22) The mixed solution obtained in step (21) was transferred to a constant temperature magnetic stirrer and stirred at 40°C for 24 hours. After the reaction was completed, the mixture was centrifuged and washed with solvent C for 3 times. The solid was vacuum dried at 60°C for 12 hours to obtain the nanomaterial grafted polystyrene maleic anhydride.

[0109] Furthermore, the catalyst is p-toluenesulfonic acid.

[0110] Furthermore, the solvent C is toluene.

[0111] Furthermore, the specific steps of step (3) are as follows:

[0112] (31) Place nanomaterial grafted polystyrene maleic anhydride, a catalyst, and 200 parts of polyether in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the nanomaterial grafted polystyrene maleic anhydride in an ultrasonic oscillator for 0.5 h to obtain a mixed solution, wherein:

[0113] The mass ratio of nanomaterial grafted polystyrene maleic anhydride, catalyst, and polyether is 0.1:0.1:1;

[0114] The amount of solvent C added is twice the amount of polyether used;

[0115] (32) The mixed solution obtained in step (31) was transferred to a constant temperature magnetic stirrer and stirred at 40°C for 24 hours. After the reaction was completed, the mixture was centrifuged and washed three times with distilled water and anhydrous ethanol respectively, and vacuum dried at 60°C for 12 hours to obtain a dual-target demulsifier.

[0116] Furthermore, the molecular weight of the polystyrene maleic anhydride is 2000.

[0117] Furthermore, based on the mass of the polystyrene maleic anhydride, the content of the structural unit derived from maleic anhydride is 5 weight %.

[0118] Furthermore, the hydrophilic nano material is nano-TiO2.

[0119] Furthermore, the particle size of the nanomaterial is 1 nm.

[0120] Furthermore, the polyether is a diblock polyether obtained by polymerizing propylene oxide and ethylene oxide with an alkyl alcohol having 4 carbon atoms as an initiator.

[0121] Furthermore, the molecular weight of the polyether is 2000.

[0122] A dual-target demulsifier is prepared by any one of the above preparation methods.

[0123] The application of any of the above dual-target demulsifiers in oil production, especially in the treatment of binary composite flooding produced fluid as a demulsifier.

[0124] Example 7

[0125] A method for preparing a dual-target demulsifier, by parts by mass, comprises the following steps:

[0126] (1) reacting 100 parts of a hydrophilic nanomaterial with dopamine hydrochloride to obtain a polydopamine-modified nanomaterial;

[0127] (2) dispersing the polydopamine-modified nanomaterial in solvent C and reacting it with 500 parts of polystyrene maleic anhydride to prepare nanomaterial grafted polystyrene maleic anhydride (SMA-g-HNM);

[0128] (3) The nanomaterial grafted polystyrene maleic anhydride is dispersed in solvent C and reacted with 800 parts of polyether. After the reaction is completed, a dual-target demulsifier is obtained.

[0129] Furthermore, the specific steps of step (1) are as follows:

[0130] (11) Take appropriate amounts of dopamine hydrochloride and 100 parts of hydrophilic nanomaterials in a reaction container, wherein:

[0131] The mass ratio of dopamine hydrochloride to the hydrophilic nanomaterial is 10:10;

[0132] (12) Add an appropriate amount of Tris-HCl buffer to the reaction container, seal it, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for 2 hours to obtain a mixed solution, wherein:

[0133] The amount of the Tris-HCl buffer is 20 times the mass of the hydrophilic nanomaterial;

[0134] (13) transferring the mixed solution obtained in step (12) to an oscillator and oscillating at room temperature for 8 hours to obtain a reaction solution (dopamine hydrochloride is polymerized to form polydopamine hydrochloride, which adheres to the surface of the hydrophilic nanomaterial, and the catechol groups in the polydopamine hydrochloride react with the hydroxyl groups on the surface of the hydrophilic nanomaterial to achieve loading);

[0135] (14) The reaction solution obtained in step (13) is centrifuged, then washed with ultrapure water and anhydrous ethanol for 5 times, and vacuum dried at 60° C. for 12 h. After completion, a polydopamine-modified nanomaterial is obtained.

[0136] Furthermore, in step (13), the mixed solution obtained in step (12) is transferred to an oscillator and oscillated at a frequency of 300 rpm at room temperature for 4 hours.

[0137] Furthermore, step (2) comprises the following steps:

[0138] (21) Place polydopamine-modified nanomaterials, a catalyst, and 500 parts of polystyrene maleic anhydride in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the mixture in an ultrasonic oscillator for 2 hours to obtain a mixed solution, wherein:

[0139] The mass ratio of polydopamine modified nanomaterial, catalyst, and polystyrene maleic anhydride is 1:1:1;

[0140] The amount of solvent C added is 6 times the amount of polystyrene maleic anhydride used;

[0141] (22) The mixed solution obtained in step (21) was transferred to a constant temperature magnetic stirrer and stirred at 120° C. for 4 h. After the reaction was completed, the mixture was centrifuged and washed with solvent C for 5 times. The solid was vacuum dried at 80° C. for 12 h to obtain the nanomaterial grafted polystyrene maleic anhydride.

[0142] Furthermore, the catalyst is sulfuric acid. In another embodiment, the catalyst is hydrochloric acid. In another embodiment, the catalyst is phosphoric acid.

[0143] Further, the solvent C is toluene. In another embodiment, the solvent C is a mixture of equal masses of toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, dioxane, dimethyl sulfoxide, and N-methylpyrrolidone. In another embodiment, the solvent C is xylene. In another embodiment, the solvent C is N,N-dimethylformamide. In another embodiment, the solvent C is N,N-dimethylacetamide. In another embodiment, the solvent C is tetrahydrofuran. In another embodiment, the solvent C is dioxane. In another embodiment, the solvent C is dimethyl sulfoxide. In another embodiment, the solvent C is N-methylpyrrolidone.

[0144] Furthermore, the specific steps of step (3) are as follows:

[0145] (31) Place nanomaterial grafted polystyrene maleic anhydride, a catalyst, and 800 parts of polyether in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the nanomaterial grafted polystyrene maleic anhydride in an ultrasonic oscillator for 2 hours to obtain a mixed solution, wherein:

[0146] The mass ratio of nanomaterial grafted polystyrene maleic anhydride, catalyst, and polyether is 1:1:1;

[0147] The amount of solvent C added is 6 times the amount of polyether;

[0148] (32) The mixed solution obtained in step (31) was transferred to a constant temperature magnetic stirrer, stirred and reacted at 120° C. for 4 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water and anhydrous ethanol for 5 times, and vacuum dried at 80° C. for 12 h to obtain a dual-target demulsifier.

[0149] Furthermore, the molecular weight of the polystyrene maleic anhydride is 100,000.

[0150] Furthermore, based on the mass of the polystyrene maleic anhydride, the content of the structural unit derived from maleic anhydride is 50 weight %.

[0151] Further, the hydrophilic nanomaterial is nano-TiO2. In another embodiment, the hydrophilic nanomaterial is nano-ZnO. In another embodiment, the hydrophilic nanomaterial is nano-SiO2. In another embodiment, the hydrophilic nanomaterial is graphene oxide. In another embodiment, the hydrophilic nanomaterial is carbon nanotube. In another embodiment, the hydrophilic nanomaterial is a mixture of nano-TiO2, nano-ZnO, nano-SiO2, graphene oxide, and carbon nanotube in equal mass ratio.

[0152] Furthermore, the particle size of the nanomaterial is 100 nm.

[0153] Further, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using an alkyl alcohol with a carbon number of 18 as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using an alkyl alcohol with a carbon number of 12 as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using an alkylamine with a carbon number of 4 as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using an alkylamine with a carbon number of 18 as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using an alkylamine with a carbon number of 8 as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using propylene glycol as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using glycerol as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using pentaerythritol as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using polyethylene polyamine as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using polyethyleneimine as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using phenolamine resin as an initiator. In another embodiment, the polyether is a phenolic resin. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using polyamide-amine as an initiator. In another embodiment, the polyether is a diblock polyether polymerized with propylene oxide and ethylene oxide using a mixture of an alkyl alcohol with a carbon number of 6, an alkylamine with a carbon number of 9, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethyleneimine, phenolamine resin, phenolic resin, and polyamide-amine in equal mass ratios as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkyl alcohol with a carbon number of 4 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkyl alcohol with a carbon number of 18 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkyl alcohol with a carbon number of 14 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkylamine with a carbon number of 4 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkylamine with a carbon number of 18 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkylamine with a carbon number of 12 as an initiator.In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using propylene glycol as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using glycerol as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using pentaerythritol as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using polyethylene polyamine as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using polyethyleneimine as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using phenolamine resin as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using a phenolic resin as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using polyamide-amine as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using a mixture of an alkyl alcohol with a carbon number of 8, an alkylamine with a carbon number of 12, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethyleneimine, phenolic amine resin, phenolic resin, and polyamide-amine in equal mass ratios as an initiator, and propylene oxide, ethylene oxide, and propylene oxide. In another embodiment, the polyether is a triblock polyether polymerized with propylene oxide, ethylene oxide, and propylene oxide using an alkyl alcohol with a carbon number of 4 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using an alkyl alcohol with a carbon number of 18 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using an alkyl alcohol with a carbon number of 12 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using an alkylamine with a carbon number of 4 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using an alkylamine with a carbon number of 18 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using an alkylamine with a carbon number of 12 as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using propylene glycol as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using glycerol as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using pentaerythritol as an initiator.In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using polyethylene polyamine as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using polyethylene imine as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using phenolamine resin as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using phenolic resin as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using polyamide-amine as an initiator. In another embodiment, the polyether is a triblock polyether polymerized with ethylene oxide, propylene oxide, and ethylene oxide using a mixture of an alkyl alcohol with a carbon number of 4, an alkylamine with a carbon number of 4, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethyleneimine, phenolamine resin, phenolic resin, and polyamide-amine in equal mass ratios as initiators.

[0154] Furthermore, the molecular weight of the polyether is 50,000.

[0155] A dual-target demulsifier is prepared by any one of the above preparation methods.

[0156] The application of any of the above dual-target demulsifiers in oil production, especially in the treatment of binary composite flooding produced fluid as a demulsifier.

[0157] Example 8

[0158] A method for preparing a dual-target demulsifier, by parts by mass, comprises the following steps:

[0159] (1) reacting 100 parts of a hydrophilic nanomaterial with dopamine hydrochloride to obtain a polydopamine-modified nanomaterial;

[0160] (2) dispersing the polydopamine-modified nanomaterial in solvent C and reacting it with 300 parts of polystyrene maleic anhydride to prepare nanomaterial grafted polystyrene maleic anhydride (SMA-g-HNM);

[0161] (3) The nanomaterial grafted polystyrene maleic anhydride is dispersed in solvent C and reacted with 400 parts of polyether. After the reaction is completed, a dual-target demulsifier is obtained.

[0162] Furthermore, the specific steps of step (1) are as follows:

[0163] (11) Take appropriate amounts of dopamine hydrochloride and 100 parts of hydrophilic nanomaterials in a reaction container, wherein:

[0164] The mass ratio of dopamine hydrochloride to hydrophilic nanomaterial is 5:10;

[0165] (12) Add an appropriate amount of Tris-HCl buffer to the reaction container, seal it, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for 1 hour to obtain a mixed solution, wherein:

[0166] The amount of the Tris-HCl buffer is 10 times the mass of the hydrophilic nanomaterial;

[0167] (13) transferring the mixed solution obtained in step (12) to an oscillator and oscillating at room temperature for 6 hours to obtain a reaction solution (dopamine hydrochloride is polymerized to form polydopamine hydrochloride, which adheres to the surface of the hydrophilic nanomaterial, and the catechol groups in the polydopamine hydrochloride react with the hydroxyl groups on the surface of the hydrophilic nanomaterial to achieve loading);

[0168] (14) The reaction solution obtained in step (13) is centrifuged, then washed with ultrapure water and anhydrous ethanol four times in sequence, and vacuum dried at 45° C. for 16 h. After completion, a polydopamine-modified nanomaterial is obtained.

[0169] Furthermore, in step (13), the mixed solution obtained in step (12) is transferred to an oscillator and oscillated at a frequency of 200 rpm at room temperature for 12 hours.

[0170] Furthermore, step (2) comprises the following steps:

[0171] (21) Place polydopamine-modified nanomaterials, a catalyst, and 300 parts of polystyrene maleic anhydride in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the mixture in an ultrasonic oscillator for 1 hour to obtain a mixed solution, wherein:

[0172] The mass ratio of polydopamine modified nanomaterial, catalyst, and polystyrene maleic anhydride is 0.5:0.5:1;

[0173] The amount of solvent C added is 4 times the amount of polystyrene maleic anhydride used;

[0174] (22) The mixed solution obtained in step (21) was transferred to a constant temperature magnetic stirrer and stirred at 80° C. for 12 h. After the reaction was completed, the mixture was centrifuged and washed with solvent C for 4 times. The solid was vacuum dried at 70° C. for 16 h to obtain the nanomaterial grafted polystyrene maleic anhydride.

[0175] Furthermore, the catalyst is hydrochloric acid.

[0176] Furthermore, the solvent C is N,N-dimethylformamide.

[0177] Furthermore, the specific steps of step (3) are as follows:

[0178] (31) Place nanomaterial grafted polystyrene maleic anhydride, a catalyst, and 400 parts of polyether in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the nanomaterial grafted polystyrene maleic anhydride in an ultrasonic oscillator for 1 hour to obtain a mixed solution, wherein:

[0179] The mass ratio of nanomaterial grafted polystyrene maleic anhydride, catalyst, and polyether is 0.5:0.5:1;

[0180] The amount of solvent C added is 4 times the amount of polyether used;

[0181] (32) The mixed solution obtained in step (31) was transferred to a constant temperature magnetic stirrer and stirred at 60° C. for 12 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water and anhydrous ethanol for 4 times, and vacuum dried at 70° C. for 16 h to obtain a dual-target demulsifier.

[0182] Furthermore, the molecular weight range of the polystyrene maleic anhydride is 40,000.

[0183] Furthermore, based on the mass of the polystyrene maleic anhydride, the content of the structural unit derived from maleic anhydride is 26.2 wt %.

[0184] Furthermore, the hydrophilic nano material is nano-SiO2.

[0185] Furthermore, the particle size of the nanomaterial is 20 nm.

[0186] Furthermore, a triblock polyether is prepared by polymerizing an alkyl alcohol having 6 carbon atoms with ethylene oxide, propylene oxide and ethylene oxide as an initiator.

[0187] Furthermore, the molecular weight of the polyether is 20,000.

[0188] A dual-target demulsifier is prepared by any one of the above preparation methods.

[0189] The application of any of the above dual-target demulsifiers in oil production, especially in the treatment of binary composite flooding produced fluid as a demulsifier.

[0190] Example 9

[0191] The method is substantially the same as Example 8, except that in step (1), tannic acid is used to modify the hydrophilic nanomaterial to obtain tannic acid-modified nanomaterial:

[0192] Furthermore, the product of step (1) is a tannic acid-modified nanomaterial, and the specific steps are as follows, based on mass parts:

[0193] S11, taking an appropriate amount of tannic acid and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0194] The mass ratio of the tannic acid to the hydrophilic nanomaterial is 0.1:10;

[0195] S12, adding solvent A to the reaction container, sealing it, and ultrasonically dispersing the hydrophilic nanomaterials in an ultrasonic oscillator for 2 hours to obtain a mixed solution, wherein:

[0196] The amount of solvent A added is twice the mass of the hydrophilic nanomaterial;

[0197] S13, transferring the mixed solution obtained in step S12 to an oscillator and oscillating at room temperature for 4 hours to obtain a reaction solution; (in the above process, tannic acid adheres to the surface of the hydrophilic nanomaterial to achieve loading);

[0198] S14, centrifuging the reaction solution obtained in step S13, washing it with ultrapure water and anhydrous ethanol three times in sequence, and vacuum drying it at 30° C. for 24 hours to obtain the tannic acid-modified nanomaterial.

[0199] Furthermore, the solvent A is N,N-dimethylformamide.

[0200] Furthermore, in step S13, the mixed solution obtained in step S12 is transferred to an oscillator and oscillated at a frequency of 100 rpm at room temperature for 24 hours.

[0201] Example 10

[0202] The method is substantially the same as Example 8, except that in step (1), tannic acid is used to modify the hydrophilic nanomaterial to obtain tannic acid-modified nanomaterial:

[0203] Furthermore, the product of step (1) is a tannic acid-modified nanomaterial, and the specific steps are as follows, based on mass parts:

[0204] S11, taking an appropriate amount of tannic acid and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0205] The mass ratio of the tannic acid to the hydrophilic nanomaterial is 10:10;

[0206] S12, adding solvent A to the reaction container, sealing, and ultrasonically dispersing the hydrophilic nanomaterial in an ultrasonic oscillator for 6 hours to obtain a mixed solution, wherein:

[0207] The amount of solvent A added is 20 times the mass of the hydrophilic nanomaterial;

[0208] S13, transferring the mixed solution obtained in step S12 to an oscillator and oscillating at room temperature for 8 hours to obtain a reaction solution; (in the above process, tannic acid adheres to the surface of the hydrophilic nanomaterial to achieve loading);

[0209] S14, centrifugally separating the reaction solution obtained in step S13, washing it with ultrapure water and anhydrous ethanol for 5 times in sequence, and vacuum drying it at 60° C. for 12 h to obtain the tannic acid-modified nanomaterial.

[0210] Furthermore, the solvent A is N,N-dimethylacetamide.

[0211] Furthermore, in step S13, the mixed solution obtained in step S12 is transferred to an oscillator and oscillated at a frequency of 300 rpm for 4 hours at room temperature.

[0212] Embodiment 11

[0213] The method is substantially the same as Example 8, except that in step (1), tannic acid is used to modify the hydrophilic nanomaterial to obtain tannic acid-modified nanomaterial:

[0214] Furthermore, the product of step (1) is a tannic acid-modified nanomaterial, and the specific steps are as follows, based on mass parts:

[0215] S11, taking an appropriate amount of tannic acid and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0216] The mass ratio of the tannic acid to the hydrophilic nanomaterial is 5:10;

[0217] S12, adding solvent A to the reaction container, sealing, and ultrasonically dispersing the hydrophilic nanomaterial in an ultrasonic oscillator for 3 hours to obtain a mixed solution, wherein:

[0218] The amount of solvent A added is 10 times the mass of the hydrophilic nanomaterial;

[0219] S13, transferring the mixed solution obtained in step S12 to an oscillator and oscillating at room temperature for 6 hours to obtain a reaction solution; (in the above process, tannic acid adheres to the surface of the hydrophilic nanomaterial to achieve loading);

[0220] S14, centrifugally separating the reaction solution obtained in step S13, washing it with ultrapure water and anhydrous ethanol for 4 times in sequence, and vacuum drying it at 50° C. for 16 h to obtain the tannic acid-modified nanomaterial.

[0221] Furthermore, the solvent A is tetrahydrofuran. In another embodiment, the solvent A is 1,4-dioxane. In another embodiment, the solvent A is dimethyl sulfoxide. In another embodiment, the solvent A is N-methylpyrrolidone. In another embodiment, the solvent A is a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, 1,4-dioxane, dimethyl sulfoxide, and N-methylpyrrolidone in equal mass ratios.

[0222] Furthermore, in step S13, the mixed solution obtained in step S12 is transferred to an oscillator and oscillated at a frequency of 200 rpm at room temperature for 12 hours.

[0223] Example 12

[0224] The method is substantially the same as Example 8, except that in step (1), a silane coupling agent is used to modify the hydrophilic nanomaterial to obtain a silane coupling agent-modified nanomaterial:

[0225] Furthermore, when the product of step (1) is a silane coupling agent-modified nanomaterial, the specific steps are as follows, calculated by weight:

[0226] Step 11, take an appropriate amount of silane coupling agent and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0227] The mass ratio of the silane coupling agent to the hydrophilic nanomaterial is 0.1:10;

[0228] Step 12, add solvent B to the reaction container, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for 0.5 h to obtain a mixed solution, wherein:

[0229] The amount of solvent B added is twice the mass of the hydrophilic nanomaterial;

[0230] Step 13, transfer the mixed solution obtained in step 12 to a constant temperature magnetic stirrer, and stir the mixture at 30°C for 18 hours to obtain a reaction solution;

[0231] step14. Centrifuge the reaction solution obtained in step13, wash it with ultrapure water and anhydrous ethanol three times in sequence, and vacuum dry it at 30°C for 24 hours to obtain a silane coupling agent-modified nanomaterial.

[0232] Furthermore, the solvent B is methanol.

[0233] Furthermore, the silane coupling agent is 3-aminopropyltrimethoxysilane (APTMS).

[0234] Example 13

[0235] The method is substantially the same as Example 8, except that in step (1), a silane coupling agent is used to modify the hydrophilic nanomaterial to obtain a silane coupling agent-modified nanomaterial:

[0236] Furthermore, when the product of step (1) is a silane coupling agent-modified nanomaterial, the specific steps are as follows, calculated by weight:

[0237] Step 11, take an appropriate amount of silane coupling agent and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0238] The mass ratio of the silane coupling agent to the hydrophilic nanomaterial is 10:10;

[0239] Step 12, add solvent B to the reaction container, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for 2 hours to obtain a mixed solution, wherein:

[0240] The amount of solvent B added is 20 times the mass of the hydrophilic nanomaterial;

[0241] Step 13, transfer the mixed solution obtained in step 12 to a constant temperature magnetic stirrer, and stir and react at 100°C for 2 hours to obtain a reaction solution;

[0242] step14. Centrifuge the reaction solution obtained in step13, wash it with ultrapure water and anhydrous ethanol for 6 times in sequence, and vacuum dry it at 60°C for 12 hours to obtain a silane coupling agent-modified nanomaterial.

[0243] Furthermore, the solvent B is ethanol.

[0244] Furthermore, the silane coupling agent is 3-aminopropyltriethoxysilane (KH550).

[0245] Embodiment 14

[0246] The method is substantially the same as Example 8, except that in step (1), a silane coupling agent is used to modify the hydrophilic nanomaterial to obtain a silane coupling agent-modified nanomaterial:

[0247] Furthermore, when the product of step (1) is a silane coupling agent-modified nanomaterial, the specific steps are as follows, calculated by weight:

[0248] Step 11, take an appropriate amount of silane coupling agent and 100 parts of hydrophilic nanomaterials into a reaction container, wherein:

[0249] The mass ratio of the silane coupling agent to the hydrophilic nanomaterial is 5:10;

[0250] Step 12, add solvent B to the reaction container, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for 1 hour to obtain a mixed solution, wherein:

[0251] The amount of solvent B added is 10 times the mass of the hydrophilic nanomaterial;

[0252] Step 13, transfer the mixed solution obtained in step 12 to a constant temperature magnetic stirrer, and stir the mixture at 60°C for 9 hours to obtain a reaction solution;

[0253] step14. Centrifuge the reaction solution obtained in step13, wash it with ultrapure water and anhydrous ethanol four times in sequence, and vacuum dry it at 45°C for 16 hours to obtain a silane coupling agent-modified nanomaterial.

[0254] Further, the solvent B is n-propanol. In another embodiment, the solvent B is isopropanol. In another embodiment, the solvent B is formic acid. In another embodiment, the solvent B is acetic acid. In another embodiment, the solvent B is a mixture of methanol, ethanol, n-propanol, isopropanol, formic acid and acetic acid in equal mass ratios.

[0255] Furthermore, the silane coupling agent is diethylenetriaminopropyltrimethoxysilane. In another embodiment, the silane coupling agent is a mixture of 3-aminopropyltrimethoxysilane (APTMS), 3-aminopropyltriethoxysilane (KH550), and diethylenetriaminopropyltrimethoxysilane in equal weight ratio.

[0256] Performance characterization:

[0257] Referring to the Chinese petroleum and natural gas industry standard SY / T 5281-2000 "Crude oil demulsifier performance test method (bottle test method)", the dual-target demulsifier prepared in test examples 6-14 was tested on the binary flooding produced fluid of the Gudong Oil Production Plant in Shengli Oilfield in a field bottle test.

[0258] The specific test steps are as follows:

[0259] In a 100-mL demulsification bottle, 20 mL of the oil phase (mainly W / O emulsion) and 80 mL of the water phase (mainly O / W emulsion) from the discharge fluid of the Gudong No. 2 joint well were mixed to obtain multiple complex emulsions. The mixture was kept at a constant temperature of 45°C in a water bath for 45 min. Then, 100 mg / L of the demulsifier to be tested was added to the demulsification bottle, shaken 200 times, and placed back in a constant temperature water bath to maintain a constant temperature.

[0260] Observe the oil-water phase situation after 12 hours.

[0261] Test the water content in oil and the oil content in water after demulsification.

[0262] The polymer content in the wastewater after demulsification was determined by liquid chromatography and compared with the polymer content in the produced fluid to obtain the polymer retention rate.

[0263] The experimental results are shown in Table 1. Among them, the reagents added in sequence numbers 1-4 in Table 1 are polyether demulsifier + on-site reverse demulsifier, and the concentrations of the two are 50 mg / L respectively. It can be seen from Table 1 that the dual-target demulsifier prepared by the present invention has a good demulsification clear water effect on the binary flooding produced fluid, and can retain the polymer in the sewage.

[0264] Table 1 Results of emulsion demulsification and clear water from crude oil production

[0265]

[0266]

[0267] The above describes the embodiments of the present invention in detail. However, the present invention is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A dual-target demulsifier, characterized in that: It is formed by cross-linking the anhydride groups in polystyrene maleic anhydride with hydrophilic nanomaterials and polyether, wherein: The dual-target demulsifier is composed of a structural unit A derived from polystyrene maleic anhydride, a structural unit B derived from a hydrophilic nanomaterial, and a structural unit C derived from a polyether; Based on the total mass of the dual-target demulsifier, the content of the structural unit A is 10-62.5% by weight, the content of the structural unit B is 7.1-25% by weight, and the content of the structural unit C is 25-80% by weight.

2. A method for preparing the dual-target demulsifier according to claim 1, characterized in that: The method comprises the following steps, in parts by mass: (1) reacting 100 parts of a hydrophilic nanomaterial with dopamine hydrochloride or tannic acid or a silane coupling agent, respectively, to obtain a polydopamine-modified nanomaterial or a tannic acid-modified nanomaterial or a silane coupling agent-modified nanomaterial; (2) dispersing the polydopamine-modified nanomaterial or the tannic acid-modified nanomaterial or the silane coupling agent-modified nanomaterial in solvent C, and reacting with 100-500 parts of polystyrene maleic anhydride to obtain a nanomaterial grafted with polystyrene maleic anhydride; (3) The nanomaterial grafted polystyrene maleic anhydride is dispersed in solvent C and reacted with 200-800 parts of polyether. After the reaction is completed, a dual-target demulsifier is obtained.

3. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: When the product of step (1) is a polydopamine-modified nanomaterial, the specific steps are as follows: (11) Take appropriate amounts of dopamine hydrochloride and 100 parts of hydrophilic nanomaterials in a reaction container, respectively, wherein: The mass ratio of dopamine hydrochloride to the hydrophilic nanomaterial is (0.1-10):10; (12) Add an appropriate amount of Tris-HCl buffer to the reaction container, seal it, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for at least 0.5 h to obtain a mixed solution, wherein: The amount of the Tris-HCl buffer is 2-20 times the mass of the hydrophilic nanomaterial; (13) transferring the mixed solution obtained in step (12) to an oscillator and oscillating at room temperature for at least 4 hours to obtain a reaction solution; (14) The reaction solution obtained in step (13) is centrifuged, and then washed with ultrapure water and anhydrous ethanol at least three times, and vacuum dried at 30-60° C. for at least 12 h. After completion, a polydopamine-modified nanomaterial is obtained.

4. The method for preparing a dual-target demulsifier according to claim 3, characterized in that: In step (13), the mixed solution obtained in step (12) is transferred to an oscillator and oscillated at a frequency of 100-300 rpm at room temperature for 4-24 hours.

5. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: When the product of step (1) is a tannic acid-modified nanomaterial, the specific steps are as follows, based on parts by mass: S11, taking an appropriate amount of tannic acid and 100 parts of hydrophilic nanomaterials into a reaction container, wherein: The mass ratio of the tannic acid to the hydrophilic nanomaterial is (0.1-10):10; S12, adding solvent A to the reaction container, sealing, and ultrasonically dispersing the hydrophilic nanomaterial in an ultrasonic oscillator for at least 2 hours to obtain a mixed solution, wherein: The amount of solvent A added is 2-20 times the mass of the hydrophilic nanomaterial; S13, transferring the mixed solution obtained in step S12 to an oscillator and oscillating at room temperature for at least 4 hours to obtain a reaction solution; S14, centrifugally separating the reaction solution obtained in step S13, washing with ultrapure water and anhydrous ethanol at least 3 times in sequence, and vacuum drying at 30-60° C. for at least 12 hours to obtain tannic acid-modified nanomaterials.

6. The method for preparing a dual-target demulsifier according to claim 5, characterized in that: The solvent A is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, 1,4-dioxane, dimethyl sulfoxide, and N-methylpyrrolidone; In step S13, the mixed solution obtained in step S12 is transferred to an oscillator and oscillated at a frequency of 100-300 rpm for 4-24 hours at room temperature.

7. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: When the product of step (1) is a silane coupling agent modified nanomaterial, the specific steps are as follows, calculated by weight: Step 11, take an appropriate amount of silane coupling agent and 100 parts of hydrophilic nanomaterials into a reaction container, wherein: The mass ratio of the silane coupling agent to the hydrophilic nanomaterial is (0.1-10):10; Step 12, add solvent B to the reaction container, and disperse the hydrophilic nanomaterials by ultrasonication in an ultrasonic oscillator for at least 0.5h to obtain a mixed solution, wherein: The amount of solvent B added is 2-20 times the mass of the hydrophilic nanomaterial; Step 13, transfer the mixed solution obtained in step 12 to a constant temperature magnetic stirrer, and stir the mixture at 30-100°C for 2-18h to obtain a reaction solution; step14. Centrifuge the reaction solution obtained in step13, wash it with ultrapure water and anhydrous ethanol at least 3 times in sequence, and vacuum dry it at 30-60°C for at least 12 hours to obtain a silane coupling agent-modified nanomaterial.

8. The method for preparing a dual-target demulsifier according to claim 7, characterized in that: The solvent B is at least one of methanol, ethanol, n-propanol, isopropanol, formic acid and acetic acid; The silane coupling agent is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and diethylenetriaminopropyltrimethoxysilane.

9. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: Step (2) comprises the following steps: (21) Place polydopamine-modified nanomaterials or tannic acid-modified nanomaterials or silane coupling agent-modified nanomaterials, a catalyst, and 100-500 parts of polystyrene maleic anhydride in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse in an ultrasonic oscillator for at least 0.5 h to obtain a mixed solution, wherein: The mass ratio of the polydopamine modified nanomaterial or the tannic acid modified nanomaterial or the silane coupling agent modified nanomaterial, the catalyst, and the polystyrene maleic anhydride is (0.1-1):(0.1-1):1; The amount of solvent C added is 2-6 times the amount of polystyrene maleic anhydride used; (22) The mixed solution obtained in step (21) is transferred to a constant temperature magnetic stirrer, and the mixture is stirred at 40-120° C. for 4-24 hours. After the reaction is completed, the mixture is centrifuged, and the solid is washed with solvent C for at least 3 times, and vacuum dried at 60-80° C. for at least 12 hours to obtain the nanomaterial grafted polystyrene maleic anhydride.

10. The method for preparing a dual-target demulsifier according to claim 9, characterized in that: The solvent C is at least one of toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, dioxane, dimethyl sulfoxide, and N-methylpyrrolidone.

11. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: The specific steps of step (3) are as follows: (31) Place nanomaterial grafted polystyrene maleic anhydride, a catalyst, and 200-800 parts of polyether in a reaction container, then add solvent C to the reaction container, and ultrasonically disperse the nanomaterial grafted polystyrene maleic anhydride in an ultrasonic oscillator for at least 0.5 h to obtain a mixed solution, wherein: The mass ratio of nanomaterial grafted polystyrene maleic anhydride, catalyst and polyether is (0.1-1):(0.1-1):1; The amount of solvent C added is 2-6 times the amount of polyether used; (32) The mixed solution obtained in step (31) is transferred to a constant temperature magnetic stirrer, stirred and reacted at 40-120° C. for 4-24 hours. After the reaction is completed, the mixture is centrifuged and washed with distilled water and anhydrous ethanol at least 3 times in sequence, and vacuum dried at 60-80° C. for at least 12 hours to obtain a dual-target demulsifier.

12. The method for preparing a dual-target demulsifier according to claim 11, characterized in that: The catalyst is one of p-toluenesulfonic acid, sulfuric acid, hydrochloric acid and phosphoric acid.

13. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: The molecular weight of the polystyrene maleic anhydride is in the range of 2000-100000.

14. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: Based on the mass of the polystyrene maleic anhydride, the content of the structural unit derived from maleic anhydride is 5-50% by weight.

15. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: The hydrophilic nanomaterial is at least one of nano-TiO2, nano-ZnO, nano-SiO2, graphene oxide, and carbon nanotubes; The particle size of nanomaterials is 1-100nm.

16. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: The polyether is a diblock polyether obtained by polymerizing propylene oxide or ethylene oxide with at least one of alkyl alcohols with 4 to 18 carbon atoms, alkylamines with 4 to 18 carbon atoms, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethylene imine, phenolamine resin, phenolic resin, and polyamide-amine as an initiator, or A triblock polyether polymerized with propylene oxide, ethylene oxide, or propylene oxide using at least one of an alkyl alcohol having 4 to 18 carbon atoms, an alkylamine having 4 to 18 carbon atoms, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethylene imine, phenolamine resin, phenolic resin, and polyamide-amine as an initiator; or A triblock polyether prepared by polymerizing at least one of an alkyl alcohol having 4 to 18 carbon atoms, an alkylamine having 4 to 18 carbon atoms, propylene glycol, glycerol, pentaerythritol, polyethylene polyamine, polyethylene imine, phenolamine resin, phenolic resin and polyamide-amine as an initiator with ethylene oxide, propylene oxide and ethylene oxide.

17. The method for preparing a dual-target demulsifier according to claim 2, characterized in that: The molecular weight of the polyether is 2000-50000.

18. A dual-target demulsifier, characterized in that: Prepared by the preparation method described in any one of claims 2 to 17.

19. Use of the dual-target demulsifier according to claim 1 or claim 18 in oil production, especially as a demulsifier in treating binary composite flooding produced fluid.

Citation Information

Patent Citations

  • Preparation method of magnetic graphene oxide demulsifying agent

    CN106219669A

  • A demulsifier and its preparation method

    CN109054888B

  • A reusable carbon-based nano-demulsifier and its preparation method

    CN110559691B